Vocational High School (SMK) Students Accounting Competence Prediction Model by Using Astin I-E-O Model - Defi Sri Harwati; Heri Yanto (Dinamika Pendidikan, 2018)
This research aims to know the descriptive of input, environment, and outcome; analyze the influence of input to outcome; analyze the influence of environment to outcome; analyze the influence of input to environement; and analyze the role of environment in mediating the influence of input to outcome. Student previous achievement consisting of Mathematics and Indonesian National Exam at Junior High School is the educational input. Student engagement consisting of school engagement and class engagement is the educational environment and student accounting competence is the educational outcome. This research was a quantitative research. Data analysis used descriptive and path analysis technique. The total population and sample consists of 128 students of first class accounting. The results and conclusions in this study indicate that accounting competence is still good, student engagement is good, and student previous achievement is very good. There are influences of mathematics National Exam, Indonesian National Exam, school engagement, and class engagement on student accounting competence; there are influences of Mathematics and the Indonesian National Exam on school engagement and class engagement. School engagement mediates the influence of mathematics National Exam on accounting competence, but it does not mediate the influence of the Indonesian National Exam on accounting competence. Then, class engagement mediates the influences of the mathematics and Indonesian National Exam on accounting competencies.